Implementation of the Measured Fishing Policy-Penangkapan Ikan Terukur (PIT) in the Riau Islands Province - Dicky Novalino; Niken Wulandari (Journal of Maritime Policy Science, 2024)
The implementation of the Measured Fishing Policy/Penangkapan Ikan Terukur (PIT) in the Riau Islands Province is a strategic step to manage fishery resources sustainably. The background of this study focuses on the challenges faced in the implementation of the PIT policy, including filling in logbooks by 10-30 GT fishing vessels, conflicts between traditional fishermen and industry players, and limited supporting infrastructure. This study aims to analyze the implementation of the PIT policy using the Van Meter and Van Horn theory, which refers to four main indicators: communication, resources, bureaucratic structure, and implementer disposition. The research method used is a descriptive qualitative approach, with secondary data collection and triangulation analysis to increase validity and reliability. The results of the study indicate that the implementation of the PIT policy in the Riau Islands still faces obstacles in the form of uneven communication, lack of skilled human resources, and inadequate infrastructure. The complex bureaucratic structure also hinders the efficiency of policy implementation. However, government efforts, such as policy socialization through training and the establishment of the Fisheries Management Institution (LPP) in WPPNRI 711, have begun to show positive impacts. In conclusion, the successful implementation of the PIT policy requires a holistic approach that includes strengthening human resources, infrastructure investment, bureaucratic reform, and inclusive communication strategies. Thus, this policy is expected to contribute to the sustainability of marine ecosystems and the welfare of coastal communities in the Riau Islands Province